Translating transcription: proteomics in chronic rhinosinusitis with nasal polyps reveals significant discordance with messenger RNA expression. Issue 7 (18th February 2019) - Workman, Alan D.; Nocera, Angela L.; Mueller, Sarina K.; Otu, Hasan H.; Libermann, Towia A.; Bleier, Benjamin S.
Abstract : Background: Much of the literature examining chronic rhinosinusitis with nasal polyps (CRSwNP) immunopathology has been predicated on messenger RNA (mRNA) analysis with the assumption that transcriptional changes would reflect end‐effector protein expression. The purpose of this study was to test this hypothesis using matched transcriptomic and proteomic data sets. Methods: Matched tissue proteomic and transcriptomic arrays were quantified in CRSwNP polyp tissue and control inferior turbinate tissue (n = 10/group). Mucus samples were additionally collected in 6 subjects from each group. Proteins were grouped into functional categories by bioinformatics and differential expression analyses. Log‐log regression and Pearson correlations were performed to determine the level of agreement between data sets. Results: Of the 1310 proteins examined, 393 were significantly differentially expressed in CRSwNP. On regression analysis, differences in protein expression were poorly predicted by differences in mRNA expression ( R 2 = 0.020, p < 0.05). Several genes canonically thought to be overexpressed in CRSwNP, including IL‐5, IL‐13, TSLP, CCL13, and CCL26, showed substantial increases in mRNA transcription, but had minimally or unchanged protein expression. Others, including IgE, periostin, CCL18, and CST1/2, were increased at both the transcriptomic and proteomic levels. Among differentially regulated proteins, tissue and mucus protein levels showed weak correlation ( r = 0.26, p < 0.0001). Conclusion: Proteomic analysis in CRSwNP has revealed novel disease‐associated proteins and pathways, yet correlates poorly with transcriptomic data. The increasing availability of proteomic arrays opens the door to new potential explanatory mechanisms in CRSwNP and suggests that mRNA based studies should be validated with protein analysis.